Study of Electrical Properties of Nano TiO2 Coatings Based on the Characteristic Matrix Theory and the Brus Model - Hijab, Sarah A.; Al-Rashid, Saeed N. Turki (East European Journal of Physics, 2022)
Electrical properties of Nano TiO2 coatings as a function of the nanoparticle size have been studied. In addition, this study explores how to calculate the quantum confinement energy of TiO2. The results confirm the effect of particle size on electrical properties especially when the size becomes close to the exciton Bohr radius. The electrical properties are not effected when the size becomes close to 40 nm. The Bohr radius of Nano TiO2 coatings has been found to be 1.4 nm. While the confinement energy was 0.43 eV. The program depends on the Characteristic Matrix Theory and The Brus Model.